Oxidative stress as a predictor of cataract surgery outcomes - M. A. Kovalevskaya; N. V. Vedrintseva (Oftalʹmologiâ)
Exhaustion of anti-oxidative potential and oxidative stress are considered as trigger mechanisms of cataract development. Products of free radical oxidation are accumulated in lens. Decrease in water solubility of proteins results in the sorption of uncharged proteins on cellular membranes. This affects regular lenticular membrane folding. Light scattering on folded membranes of lenticular fibers is considered as a primary cause of lens opacities in cataract. Most problems occur in complicated cataract surgery as its development is associated with background diseases, ocular pathology, and external factor exposure. Aim. To increase the efficacy of cataract treatment in metabolic syndrome patients. Materials and methods. 115 cataract patients (230 eyes) were examined. All patients have undergone detailed clinical and complex eye examination and were divided into 2 groups depending on cataract genesis. In group 1 (age-related cataracts), somatic disorders were diagnosed in 4.5% of cases, in group 2 (complicated cataracts), somatic disorders were diagnosed in 100% of cases. Tear and blood tests were performed. Tear level of active peroxiredoxin 6 (PRDX6) and/or its breakdown fragments in fluid and blood level of metabolic syndrome markers were studied. Results. The expression of oxidative stress protective enzymes in tear fluid was investigated. Comparative assessment of tear antioxidant enzyme activity under oxidative stress in therapeutic and surgical procedures (phaco and ECCE) was performed. Post-operatively, PRDX6 increase was revealed in age-related cataract patients. This is confirmed by the absence of phaco complications. In complicated cataract, PRDX6 level was 6 times lower than in age-related cataract patients. Conclusions. Dynamic analysis of laboratory tests in complicated cataract patients confirmed or disproved the presence of general metabolic disorders and oxidative stress development. Tear proteomic profile and blood metabolic disorder parameters served as a basis for selective choice of topical and systemic antioxidant agents to prevent and stabilize lens opacities.